Protocolised Approach to End-of-Life Care in the ICU—The ICU PALCare Pilot Project. Issue 3 (May 2015) - Rajamani, A.; Barrett, E.; Weisbrodt, L.; Bourne, J.; Palejs, P.; Gresham, R.; Huang, S.
International literature on end-of-life care in intensive care units (ICUs) supports the use of 'protocol bundles', which is not common practice in our 18-bed adult general ICU in Sydney, New South Wales. We conducted a prospective observational study to identify problems related to end-of-life care practices and to determine whether there was a need to develop protocol bundles. Any ICU patient who had 'withdrawal' of life-sustaining treatment to facilitate a comfortable death was eligible. Exclusion criteria included organ donors, unsuitable family dynamics and lack of availability of research staff to obtain family consent. Process-of-care measures were collected using a standardised form. Satisfaction ratings were obtained using de-identified questionnaire surveys given to the healthcare staff shortly after the withdrawal of therapy and to the families 30 days later. Twenty-three patients were enrolled between June 2011 and July 2012. Survey questionnaires were given to 25 family members and 30 healthcare staff, with a high completion rate (24 family members [96%] and 28 staff [93.3%]). Problems identified included poor documentation of family meetings (39%) and symptom management. Emotional/spiritual support was not offered to families (39.1%) or ICU staff (0%). The overall level of end-of-life care was good. The overwhelming majority of families and healthcare staff were highly satisfied with the care provided. Problems identified related to communication documentation and lack of spiritual/emotional support. To address these problems, targeted measures would be more useful than the adoption of protocol bundles. Alternate models of satisfaction surveys may be needed.